Hermenêutica e aplicação da convenção de condomínio: (propriedade horizontal) - Fazano, Haroldo Guilherme Vieira (2007)
This thesis has for objective to elaborate a scientific study regarding the interpretation and of the application of the condominium convention (horizontal property) that it was carried through in three phases, legal analysis, logical concentration and legal construction, and that is justified for the necessity of bigger legal security on the subject. In the legal analysis, we investigate the similar elements of the horizontal property and justinian codes, distinguishing them and separating them. In the logical concentration, we regroup these same elements, extracting of them general rules, especially regarding the condominium convention. In the legal construction, we determine the essential characteristics that they individualized it, reducing it it a general category, with organized proper types so that it can be seen its fulness. In the two first phases, we made a brought up to date study of the horizontal property, pointing its period of training in Brazil and diverse countries. We verify this new model of property, since its birth until its extinguishing (denomination, legal nature, object, constitution, requirements, specification of condominium, convention, acts, rights and duties of the joint owners and administration of the condominium), beyond studying innumerable similar justinian codes (the principles of right, the autonomy of the will, the legal transaction and its interpretation), the theories that they look to study the right and the rights of neighborhood. How much to the condominium convention demons its concept and its legal nature, we study the legal relationship in the horizontal property and analyze the agreements of the national doctrine and the jurisprudence, with intention to investigate as she has been carried through the interpretation of the diverse situations that occur in the horizontal property, in special concerning the condominium convention. Already in its phase of legal construction, this thesis arrived at the following general results: 1) schematized the condominium convention, how much to its origin; 2) schematized its institucional norms in, of administration, statutory, how much to the penalties and generalities. From them, it arrived at the following specific results: 1) studied the convention how much to its origin and established the criterion of the qualified majority for its validity; 2) classified the institutional norms, struck the criterion of the qualified majority and indicated quorum of 2/3 for the alteration of the convention, denying the existence of stony clause, perfect legal act and acquired right; 3) established the application of principles in the requirement of the management or administration norms: ) how much to the expenditures, it specified them and it concluded for the application of the general criterion of the proportionality; b) how much to the agencies, it classified them in deliberative, executive and advisory, pointing its functions, species, functioning and establishing the application of the criterion of the superiority in the interpretation of the rules that these agencies discipline; 4) with respect to the statutory norms classified the rights and duties, indicating its principles and rules, especially how much: extension, criteria, incidence, interpretation, form, setting and prohibitions; 5) with regard to the norms that establish penalties to the infractions, wrote down its concept, its requirement (vagueness doctrine), the responsibility of the agent and the penalties that are allowed and forbidden in the horizontal property; 6) divided the allowed and forbidden general rules in and fixed its reach